Encyclopedia of Internet technologies and applications - Freire, Mario Marques 1969-.; Periera, Manuela; Gale Group (Hershey, Penn. Information Science Reference, 2008)
Provides the most thorough examination of Internet technologies and applications for researchers in a variety of related fields. For the average Internet consumer, as well as for experts in the field of networking and Internet technologies.
Electronic reproduction.
Keywords: Internet -- Encyclopedias; Web services; Application software; Internet -- Computer programs; Electronic books